2019
DOI: 10.1177/0022018319858506
|View full text |Cite
|
Sign up to set email alerts
|

Battered Woman Syndrome, Diminished Responsibility and Women Who Kill: Insights from Scottish Case Law

Abstract: Using Scotland as a case study, this article maps the development of Battered Woman Syndrome in law. It looks to the potential space for development that has been created by the recent case of Graham v HM Advocate, concluding that such a more would be an important step and one with significant implications for domestic abuse policy and the treatment of female accused more widely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…In only one case, where the female accused pled guilty to culpable homicide (Hinshelwood), was responsibility for the female's offending located with the male co-accused (Crispin), yet in this case there is evidence of the historical tendency towards pathologising women who kill (McPherson, 2019;Nicolson, 1995):…”
Section: Construction Of Women As the Facilitators Of Violencementioning
confidence: 99%
“…In only one case, where the female accused pled guilty to culpable homicide (Hinshelwood), was responsibility for the female's offending located with the male co-accused (Crispin), yet in this case there is evidence of the historical tendency towards pathologising women who kill (McPherson, 2019;Nicolson, 1995):…”
Section: Construction Of Women As the Facilitators Of Violencementioning
confidence: 99%
“…During the original trial, evidence had been led from a psychologist who noted that the accused had been suffering from post-traumatic stress disorder and learned helplessness-essentially that Kim Galbraith had been suffering from BWS. Since then, the syndrome was not subjected to legal scrutiny until the case of Graham when the Appeal Court has replaced the language of BWS with the terminology of 'Battered Person's Syndrome' (BPS) and suggested that, moving forward, the language of BWS/BPS will be replaced with the more general terminology of post-traumatic stress disorder (a small but arguably positive development given the longstanding criticism of BWS (McPherson, 2019).…”
Section: The Response To Women Who Killed Their Abusersmentioning
confidence: 99%
“…Battered Woman Syndrome has been used to support defences of diminished responsibility in Scotland, which reduce murder to manslaughter if successful. McPherson (2020) argues the problem with Battered Woman Syndrome (BWS) is that it pathologises women, potentially making them less sympathetic to juries. The connection between helplessness and taking the extreme action of killing someone is difficult to reconcile.…”
Section: Women Who Killmentioning
confidence: 99%
“…The connection between helplessness and taking the extreme action of killing someone is difficult to reconcile. In Scotland, there is a move to present evidence of Post Traumatic Stress Disorder instead (McPherson, 2020). Ho and Chantagul (2017) conducted a public opinion survey about women who kill abusive partners in Thailand.…”
Section: Women Who Killmentioning
confidence: 99%